BOOK REVIEW : Kisah Masuk Islamnya Sang Mantan Pendeta (Dari suku Dayak di Kalimantan) Abdurrahman al-Islami dan Prof Abdurrazaq al Badr. Karawang: Darul Ihsan 2020. ISBN: 978-602-7545-22-9. 46 pages. - Sharifah Sophia, Wan Ahmad
This is a book that owes very much to the diligence of its editor, Abu ‘Abdil ‘Aziz Munir al-Jaza’iri. In this book, he put together a letter written by a former Christian priest from East Kalimantan and a sermon delivered by a preacher from Saudi Arabia, Syaikh Abdurrazaq ‘Abdil Muhsin al-Badr. In addition, the editor wrote the Introduction and added extensive footnoting below the text of the letter. His introduction is full of praise of the religion of Islam and its self-professed truth that draws people into submitting to God. The footnotes are laborious undertaking as they expanded upon the various gestures manifested in the letter. They did more than just passive signalling. They actively direct to particular emphasis because the footnotes are self-asserting, fully assured by the evidence furnished from the verses of the Quran and the sayings of Prophet Muhammad, also adding citations from religious scholars to increase the urgency of the appeal further. Remarkably, the Syaikh’s sermon and the notes of his disciple-editor were positioned in the starring role. Their mission was to represent the text of the letter and sublimate it into a theology-proper confession.